The Role of BRI Bank Medan Perjuangan Unit for Customer's Households, Indonesia - Rosmika, T. Enita; Mulia, Amrin; Chairy, Putra (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
This study aims is to finds out how the role of BRI Bank in Medan Perjuangan unit for customer’s households. This type of research that will be used in this study is the correlation method, which describes systematically about the influence of the KUR government program channeled by PT. BRI (Persero) Tbk. The result of this study the results of the 30 sample / debtor research, it can be concluded that the debtor feels an increase in living standards starting from increased production turnover, sales value, total profits, number of employees, and business assets after borrowing from BRI Bank Medan Perjuangan Unit. With the increase in the customer's business after making a loan to BRI Medan Perjuangan, it can be said that the loan received is well used for the business of the debtors and thus the credit assistance provided by the BRI Perjuangan Unit can be said to be effective in developing micro and small businesses.